Synthesis and computational analysis of conformationally restricted [3.2.2]- and [3.2.1]-3-azabicyclic diamines. Issue 43 (25th October 2017) - Tummalapalli, Sreedhar Reddy; Bhat, Rohit; Waitt, Craig; Eshuis, Henk; Rotella, David P.
Graphical abstract: Highlights: Expeditious synthesis of five unknown bicyclic [3.2.n] diamines (n = 1 and 2) In silico analysis flexibility reveals low barrier for boat–chair interconversion. In silico analysis reveals substituents influence conformation in [3.2.2] scaffold. Substantial overlap with low energy conformations of 1, 3-diaminopropane. Abstract: Conformational restriction is a useful approach for ligand design in organic and medicinal chemistry. This manuscript reports the facile synthesis and in silico conformational analysis of two new diastereomeric [3.2.2]-3-azabicyclic, two new [3.2.1]-3-aza-8-oxy-bicyclic and one new [3.2.1]-3-azabicyclic diamine scaffolds. A conformational analysis of these structures along with calculation of carbon–carbon/carbon–nitrogen bond angles was carried out and compared to those in the flexible 1, 3-diaminopropane template upon which they were based. It is of particular importance that these scaffolds have bond lengths and angles that can overlap with low energy conformers of the flexible diamine. Such information is useful for ligand design in organic chemistry and for development of structure activity relationships and in silico screening in medicinal chemistry.